The Effectiveness of Smart Apps Creator-Based Media Integrated With The Genre Process Approach in Improving Grade X Students’ Non-Literary Writing Skills - Erva Erva; Kastam Syamsi (Journal of Educational Sciences, 2026)
This study aims to determine the effectiveness of SAC-based media integrated with the genre process approach in improving the non-literary writing skills of Grade X senior high school students. The research employed a quasi-experimental method using a pretest–posttest control group design. The participants were tenth-grade students divided into an experimental class, which received writing instruction using SAC-based media integrated with the genre process approach, and a control class, which was taught using conventional methods. Data were collected through a written essay test on negotiation text material. The findings indicate that SAC-based media integrated with the genre process approach significantly improved students’ non-literary writing skills compared to conventional instruction. The posttest comparison between the experimental and control classes yielded a sig. (2-tailed) value of 0.001 (< 0.05), indicating a significant difference in the mean posttest scores of both groups. Furthermore, the analysis of learning improvement in the experimental class, based on pretest and posttest mean scores, also showed a sig. (2-tailed) value of 0.001 (< 0.05), confirming a significant difference before and after treatment. Overall, students taught using SAC-based media demonstrated higher improvement than those taught through conventional methods.